Unlocking potential: a dual-force-model of driving and empowering female digital entrepreneurship in a patriarchal society like China - Qian Guo; Jingting Liu; Zhixing Xu (Cogent Business & Management)
In societies dominated by patriarchal values, obstacles impede females’ entrepreneurial endeavors. Recent research suggests that digital technologies can offer female pathways to circumvent these obstacles. Despite this optimism, there is limited insight into what drives and supports females in digital entrepreneurship. Our in-depth case study of 13 female entrepreneurs finds that digital technology influences female entrepreneurship through two mechanisms: driving and empowering entrepreneurship. Driving mechanisms include increasing opportunities, lowering thresholds, opportunity evaluation, and resource integration. Empowering mechanisms include digital entrepreneurship learning, digital marketing, the digitization of products and services, and the digitization of resource acquisition. This study advances the understanding of how digital technologies serve as an affirmative action tool for female entrepreneurship in patriarchal societies, demonstrating that such technologies not only strengthen women’s entrepreneurial intentions, but also significantly enhance their entrepreneurial capabilities within the digital economy.